Complementary feeding: knowledge and perception of mothers attending paediatric outpatient department in a tertiary care hospital - Shaikh, Uzma A.; Dahake, Swati T. (International Journal Of Community Medicine And Public Health, 2019)
Background: Complementary feeding refers to food which supplements breast milk and ensures that the child continues to have enough energy protein and other nutrients to grow normally. Complementary feeding is started at 6 months of age, while continuing breast feeding. After 6 months of age breast milk alone is not enough to make an infant grow well. Methods: Cross sectional study conducted among 70 mothers coming to paediatric outpatient department. Data was collected regarding their knowledge and practices of complementary feeding. Mean, frequency table and chi-square test were used. Results: 77.1% women have sufficient knowledge about complementary feeding. 77.1% of mothers give complementary food after 6 months remaining i.e. 22.9% are unaware of age of starting it. All mothers are aware of the complementary food which is to be given to babies. 82.8% mothers properly know how to start with complementary feeds. 98.5% of mothers continue to breast feed their baby’s above 6 month. Conclusions: The study concluded that inadequate complementary feeding knowledge and practices were present among some study subjects.